Impact of divertor closure on edge plasma behavior in EAST H-mode plasmas. (21st April 2021) - Tao, Y Q; Xu, G S; Yang, Q Q; Yan, N; Jia, G Z; Meng, L Y; Liu, S C; Chen, L; Yu, Y W; Gao, W; Wang, Y M; Wang, L; et al.
Abstract: A series of H-mode discharges have been conducted in the EAST tokamak to study the effect of divertor closure on divertor neutral distribution and edge plasmas by scanning the location of the outer strike point. When the outer strike point moves close to the corner within ∼ 4.5 cm, the gauge in upper sub-divertor shows that the neutral pressure increases, and the reciprocating probe at outer mid-plane indicates that electron temperature decreases and electron density increases in the scrape-off layer (SOL). In the meantime, the tungsten impurity concentration and radiation power in the main plasma decrease remarkably, while the main plasma density and stored energy increase slightly. SOLPS-ITER simulation without particle drifts is performed to better understand the impact of divertor closure. The simulation clearly demonstrates that a more closed divertor produces more neutrals around the corner with the increase of electron density and the decrease of electron temperature in the SOL, consistent with experimental results. Furthermore, more neutrals escape the divertor region and penetrate into the pedestal region, which induces more pedestal fuelling, increasing pedestal electron density. EAST will upgrade the lower divertor with a more closed geometry. These results provide important guidance for the upcoming upgrade.